A high-performance supercapacitor of vertically-oriented few-layered graphene with high-density defects1. Issue 8 (28th February 2015) - Qi, Jun Lei; Wang, Xu; Lin, Jing Huang; Zhang, Fu; Feng, Ji Cai; Fei, Wei-Dong
<x xml:space="preserve">Abstract</x> A correlation exists between the degree of defects, wettability and supercapacitor properties of VFG grown by PECVD.